2017
DOI: 10.1007/978-1-4939-7000-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Methods of Protein Crystallization

Abstract: This chapter provides a review of different advanced methods that help to increase the success rate of a crystallization project, by producing larger and higher quality single crystals for determination of macromolecular structures by crystallographic methods. For this purpose, the chapter is divided into three parts. The first part deals with the fundamentals for understanding the crystallization process through different strategies based on physical and chemical approaches. The second part presents new appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 172 publications
0
9
0
Order By: Relevance
“…Initial crystallization screening of Tv CyP2 involved using commercial crystallization screen kits (Hampton Research, Jena Bioscience, and Qiagen, Aliso Viejo, CA, USA), 96-well Intelli-plates (Art Robbins Instruments, Sunnyvale, CA, USA) and a Phoenix robot (Art Robbins Instruments, Sunnyvale, CA, USA) at 298 K. The sitting drop vapor diffusion method [ 38 , 39 ] was used to grow crystals. The 0.6–3 µm crystals of Tv CyP2 appeared within 5 days in the commercial kit conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Initial crystallization screening of Tv CyP2 involved using commercial crystallization screen kits (Hampton Research, Jena Bioscience, and Qiagen, Aliso Viejo, CA, USA), 96-well Intelli-plates (Art Robbins Instruments, Sunnyvale, CA, USA) and a Phoenix robot (Art Robbins Instruments, Sunnyvale, CA, USA) at 298 K. The sitting drop vapor diffusion method [ 38 , 39 ] was used to grow crystals. The 0.6–3 µm crystals of Tv CyP2 appeared within 5 days in the commercial kit conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of the method benefiting from electric fields relies on the separation of the nucleation and crystal growth; it can be applied in the electric as well as the electromagnetic field. The nucleation process takes place while the current is switched off [28]. In order to perform crystallization experiments in the electric field, the specially designed crystal growth cell has to be used.…”
Section: Electric and Magnetic Fieldmentioning
confidence: 99%
“…It was reported that the current positively influences the size of protein crystals. Specifically, lower frequencies of alternating current provide less larger crystals compared to higher frequencies [28]. For the purposes of using electric current the e-crystallization cells based on vapour diffusion or batch method were made [29].…”
Section: Electric and Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations